Abdominal CT evaluation of the liver and spleen for staging mast cell tumors in dogs yields nonspecific results. Issue 3 (20th February 2019) - Hughes, Jonathan R; Szladovits, Balazs; Drees, Randi
Abstract: Canine mast cell tumor staging is commonly performed using abdominal ultrasonography and fine‐needle aspiration cytology of masses, lymph nodes, and hepatic and splenic parenchyma. Computed tomography is used for abdominal, thoracic, or whole body imaging in staging mast cell tumors in the authors' institution enabling evaluation of multiple body areas in one examination. The aim of this study was to compare the CT examinations acquired for staging of mast cell disease to their subsequent liver and spleen cytology findings. Medical records of dogs with primary mast cell tumors that underwent abdominal CT and concurrent liver and spleen aspirates were reviewed. The CT examinations were evaluated for attenuation, size, and margination of the liver and spleen. The relationship between CT findings and cytology results was analyzed. Forty‐nine dogs matched the inclusion criteria: five of forty‐nine dogs with cutaneous mast cell tumors were positive for metastasis from liver and/or spleen aspirates. Of the five dogs with cytological evidence of liver or spleen metastasis, four had normal CT liver attenuation and size, one dog had concurrent primary hepatocellular neoplasia, four dogs had abnormal splenic parenchyma (two nodular and two diffuse heterogeneity), and one dog had a normal attenuation of the spleen. In four dogs, the spleen was subjectively enlarged. Computed tomographic evaluation of the liver showed no consistent pattern associated with mast cell metastasis and did not predict cytology results. Multifocal splenic hypoattenuating lesions more commonly coincided with mast cell metastasis. Sampling of the liver and spleen remains to be considered in the absence of abnormal CT findings for full staging.